Long-Run Impacts of Increasing Tobacco Taxes : Evidence from South Africa - Fuchs, Alan; Del Carmen, Giselle; Mukong, Alfred Kechia (Washington, DC: World Bank, 2018)
Tobacco taxes are considered an effective policy tool to reduce tobacco consumption and produce long-run benefits that outweigh the costs associated with a price increase. Through this policy, some of the most adverse effects and economic costs of smoking can be reduced, including shorter life expectancy, higher medical expenses, added years of disability among smokers, and the effects of secondhand smoke. Nonetheless, tobacco taxes are often considered regressive because low-income households tend to allocate a larger share of their budgets to purchasing tobacco products. This paper uses an extended cost-benefit analysis to estimate the distributional effect of tobacco taxes on household welfare in South Africa. The analysis considers the effect on household income through an increase in tobacco prices, changes in medical expenses, and the prolongation of working years. The results indicate that a rise in tobacco prices initially generates negative income variations across all groups in the population. If benefits through lower medical expenses and an expansion in working years are considered, the negative effect is reduced, particularly in medium- and upper-bound elasticities. Consequently, the aggregate net effect is progressive and benefits the bottom deciles more than the richer ones. Overall, tobacco tax increases exert a small, but positive effect in the presence of low conditional tobacco price elasticity. If the population is more responsive to tobacco price changes (or participation elasticity estimates are included), then they would experience even more gains from the health and work benefits. More research is needed to clarify the distributional effects of tobacco taxation in South Africa.